2021
DOI: 10.3390/membranes11080585
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Based Harvesting Processes for Microalgae and Their Valuable-Related Molecules: A Review

Abstract: The interest in microalgae production deals with its role as the third generation of feedstock to recover renewable energy. Today, there is a need to analyze the ultimate research and advances in recovering the microalgae biomass from the culture medium. Therefore, this review brings the current research developments (over the last three years) in the field of harvesting microalgae using membrane-based technologies (including microfiltration, ultrafiltration and forward osmosis). Initially, the principles of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 112 publications
(212 reference statements)
0
12
0
Order By: Relevance
“…However, fouling may limit its application in membrane purification. Fortunately, researchers have addressed this problem by membrane modification or by applying diafiltration technology (Castro‐Muñoz & García‐Depraect, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, fouling may limit its application in membrane purification. Fortunately, researchers have addressed this problem by membrane modification or by applying diafiltration technology (Castro‐Muñoz & García‐Depraect, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…A lichen-like strategy for microalgae cultivation shows an optimistic scaling-up potential once its bioreactor cultivation can be related to membrane-bioreactors, whereas the lichen acts as a natural membrane for solid–liquid separation, which opens up the possibility of wastewater treatment and valorization alongside simultaneous low-cost algae harvesting. Studies have indicated the potential of combining algae cultivation and membrane-based technologies (membrane bioreactors, forward osmosis, ceramic membranes and others), which has resulted in efficient harvesting and bioremediation systems [ 43 , 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to extend the application of membrane technologies in this field, researchers may consider different factors influencing the performance of membrane separation techniques, such as operating parameters (transmembrane pressure, feed temperature, feed flow, membrane pore size), molecular interactions between membrane solutes, and, more importantly, prominent membrane fouling [ 54 , 61 ]. This latter aspect represents one of the main drawbacks of membrane technologies for long-term operation [ 56 , 62 ]. Therefore, new researchers in the field find in this point a potential research gap to further investigate and implement membrane processes in pilot and large-scale approaches.…”
Section: Discussionmentioning
confidence: 99%